Dynamic Analysis of Crane Vessel and Floating Wind Turbine during Temporary Berthing for Offshore On-Site Maintenance Operations - Jinkun Shi; Mingfeng Hu; Yifan Zhang; Xiaodong Chen; Sheng Yang; Thiago S. Hallak; Mingsheng Chen (Journal of Marine Science and Engineering, 2024)
With the increased scale and deployment of floating wind turbines in deep sea environments, jack-up installation vessels are unable to conduct maintenance operations due to limitations in water depth. This has led to the recognition of the advantages of floating cranes in offshore maintenance activities. However, the dynamic coupling between the crane and the floating wind turbine under wave and wind action can result in complex responses, which also relate to complex mooring configurations. The ability to maintain stability during maintenance operations has become a primary concern. In order to address this issue, a method of connecting a floating crane with a floating wind turbine is proposed, simulating the berthing of a floating offshore wind turbine (FOWT) to a crane. Thus, a systematic comparison was conducted with frequency- and time-domain simulation using ANSYS-AQWA software. The simulation results demonstrated the feasibility and dynamic efficiency of this novel berthing approach. Connecting the crane vessel to a floating wind turbine significantly reduced the crane tip movement. Simulations showed that the crane tip movement in the X-, Y-, and Z-directions was reduced by over 30%, which implies that it may be feasible to conduct offshore on-site maintenance operations for the FOWT by using floating crane vessels if the two bodies were properly constrained.